The Role of Majlis Taklim in Medan City: Institutional Growth, Religious Education, and Social Transformation - Nelly Agustina; Hasan Asari; Solihah Titin Sumanti (DINIKA : Academic Journal of Islamic Studies, 2024)
This study examines the historical and social development of Majlis Taklim in Medan City, focusing on its institutional evolution, the expansion of religious education, and its significant role in community empowerment. Using a qualitative methodology with a historical and social science approach, the research reveals how Majlis Taklim has grown from informal gatherings into structured institutions that not only provide religious education but also serve as centers for social and humanitarian activities. The findings highlight three key aspects: the social and political factors behind the establishment of Majlis Taklim, its formal institutional development, and the diversification of activities to include technology, social media, and targeted programs for different segments of society. Additionally, Majlis Taklim’s collaboration with governmental and religious organizations has strengthened its role in promoting Islamic values while addressing contemporary social issues. The study also identifies challenges such as limited resources, leadership issues, and the need for modernization to maintain relevance. The research concludes that Majlis Taklim plays a crucial role in shaping religious understanding, fostering social cohesion, and contributing to the social welfare of Medan’s Muslim community.